Analisis Pemanfaatan Media Wordwall Untuk Meningkatkan Pemahaman Konsep Matematika Siswa Sekolah Menengah Pertama Negeri Cerdas Bangsa - Maria Stefania; Nurul Umaya; Vinsensius Herianto Ndori (Universitas Muhammadiyah Purworejo, 2025)
The use of interactive digital learning media such as Wordwall offers an innovative approach to improving the quality of mathematics instruction at the junior high school level. This study aims to analyze the effectiveness of Wordwall in enhancing students’ conceptual understanding of mathematics at SMPN Cerdas Bangsa. Employing a descriptive qualitative method, data was collected through interviews, observations, and documentation. The findings reveal that Wordwall increases student motivation, active participation, and conceptual comprehension, particularly during the reinforcement phase. Teachers perceive the platform as flexible and adaptable to students' abilities, while students report a more engaging and interactive learning experience. However, its effectiveness diminishes when used before students have grasped the foundational concepts, and challenges such as limited internet access and teachers’ technological readiness remain. This study underscores the importance of targeted integration of digital media and the need for differentiated instruction to address students’ diverse learning needs. It contributes to the development of more contextual, adaptive, and meaningful mathematics learning strategies in the digital era.